Targeting minimal residual disease after surgery with molecular targeted therapy: the real path to a cure? - Masago, Katsuhiro; Fujita, Shiro; Yatabe, Yasushi (Journal of Thoracic Disease, 2018)
Stage II–IIIA non-small cell lung cancer (NSCLC) affects a highly heterogeneous group of patients with differences in the extent and localization of the disease, and the definition of stage II–IIIA disease has changed over time. The 5-year survival for completely resected stage II–IIIA NSCLC patients is poor (36–60%) (1). Indeed, at least one-third of patients show recurrences after surgery.